Student Real Estate Investment Funds - Jacob Kelly; Mariya Letdin (Journal of Real Estate Practice and Education)
The value of experiential learning is well established, and student-managed investment funds have been a popular tool to provide students with real-world investment opportunities in a classroom setting. In the last decade, there has been rapid growth of a new type of experiential learning tool—the real estate student managed investment fund. As of this writing, there are now 18 operational real estate student managed investment funds, a 15 fund increase over a 10-year period. Using our experience in launching a real estate student managed investment fund at Florida State University, we discuss the launch process, the operations, and the investment management involved. We also provide an overview of the student real estate investment fund landscape.